Targeting TNFR2: A Novel Breakthrough in the Treatment of Cancer - Li, Muchun; Zhang, Xiaozhen; Bai, Xueli; Liang, Tingbo (Frontiers in Oncology, 2022)
Tumour necrosis factor (TNF) receptor type II (TNFR2) is expressed in various tumour cells and some immune cells, such as regulatory T cells and myeloid-derived suppressing cells. TNFR2 contributes a lot to the tumour microenvironment. For example, it directly promotes the occurrence and growth of some tumour cells, activate immunosuppressive cells, and support immune escape. Existing studies have proved the importance of TNFR2 in cancer treatment. Here, we reviewed the activation mechanism of TNFR2 and its role in signal transduction in the tumour microenvironment. We summarised the expression and function of TNFR2 within different immune cells and the potential opportunities and challenges of targeting TNFR2 in immunotherapy. Finally, the advantages and limitations of TNFR2 to treat tumour-related diseases are discussed, and the problems that may be encountered in the clinical development and application of targeted anti-TNFR2 agonists and inhibitors are analysed.